The social anthropologist and the studied society. Investigating the dynamics of interaction relationships - Πέτρου, Μιχάλης (The Greek Review of Social Research, 2018)
This article, based on empirical research material collected from long-term on-site research of a rural community, focuses on some of the key aspects of the relationship -in all phases of the field research- between the social anthropologist and the society under observation, between the «observer» and the «the observed», the «familiar» and the «unfamiliar». By investigating the dynamics of interpersonal contacts between the main actors of ethnographic research, the paper, attempts to highlight the value and uniqueness of participating ‘from within’ in the collective life of the studied society in order to understand different ways of living.